2008
DOI: 10.2118/89755-pa
|View full text |Cite
|
Sign up to set email alerts
|

Production Strategy for Thin-Oil Columns in Saturated Reservoirs

Abstract: Summary Maximizing oil recovery in thin and ultrathin (<30 ft) oil columns is a challenge because of coning or cresting of unwanted fluids, regardless of well orientation. Significant oil is left behind above the well completion even for horizontal wells when bottom- or edge-water invasion occurs. Two depletion strategies may be enacted to improve recovery of the remaining oil. In the first option, a conventional horizontal is completed below the gas/oil contact (GOC). Once… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…The two papers (Hsiu-Hsyong 1998) and (Kabir, Agamini et al 2008) shows the advantages of a horizontally oriented grid to model long horizontal wells in thin oil rim reservoirs. It was shown that with a horizontal grid the well path can be represented exactly at its position, while in a high resolution stratigraphic grid the well has an error in the well path with undulating well paths and fluid contacts.…”
Section: Figmentioning
confidence: 99%
“…The two papers (Hsiu-Hsyong 1998) and (Kabir, Agamini et al 2008) shows the advantages of a horizontally oriented grid to model long horizontal wells in thin oil rim reservoirs. It was shown that with a horizontal grid the well path can be represented exactly at its position, while in a high resolution stratigraphic grid the well has an error in the well path with undulating well paths and fluid contacts.…”
Section: Figmentioning
confidence: 99%
“…If crude oil enters gas cap, large amount of oil will be wasted and oil recovery will be influenced. Vo [9], [10] and Kabir [11] pointed out that the key concern is therefore obtaining economic and optimal operations despite the gas and water coning effects that could confine production below commercial rates and hinder recovery. Therefore, coordinated development of gas cap and oil ring has been an ideal way to recover resources in gas-cap reservoirs, Kuppe [12] have confirmed it by considering concurrent gas and oil production from the Virginia Hills Belloy field.…”
Section: Introductionmentioning
confidence: 99%
“…300 m water depth, and is operated by Statoil. It is primarily a gas field, but also contains a thin oil zone with thickness varying from zero to 26 m. The use of horizontal wells has resulted in a successful recovery of this oil zone, which initially was regarded as challenging to produce due to coning and cusping of both water and gas-typical for thin oil zone production [4,7,9,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Only a part of the vertical section, including the oil leg, is shown in (confidential) internal reports. During the last few decades, such grids have been used in different contexts and with apparent success, e.g., Hsu [6] and Kabir et al [7]. However, all these models were used as ad hoc tools, and no attempts were made to assess the quality of the horizontal grid models versus traditional geo-grids.…”
Section: Introductionmentioning
confidence: 99%